An Expert System To Diagnose Febris Convulsion Disease Using Certainty Factor Method - Reski Wahyu Illahi; Maryanigsih Maryanigsih; Eko Suryana (Fakultas Ilmu Komputer Universitas Dehasen Bengkulu, 2023)
The expert system for diagnosing febris convulsion (febrile seizures) at the Regional General Hospital of Kepahiang was built using the PHP programming language and MySQL database, which can be accessed online via the link http://febriskonvulsi.vad.my.id/. This expert system has implemented the Certainty Factor Method which is used to determine the level of confidence in the perceived symptoms of the disease based on the user's CF value and the expert's CF value. With this expert system diagnosing febrile convulsions (febrile seizures), it can help patients/people who want treatment to find out the initial diagnosis of febrile convulsions based on the symptoms that are felt. Based on the system testing that has been done, it can be concluded that the functionality of the application has been running well and this expert system can provide consultation results for the diagnosis of febrile convulsions based on the symptoms selected by the user through the stages of the Certainty Factor method.